EVALUASI DESAIN JALAN KOTA BARU LAMPUNG MENURUT KAIDAH-KAIDAH PENGEMBANGAN WILAYAH BERWAWASAN LINGKUNGAN - Zulkarnain Sero (Inovasi Pembangunan : Jurnal Kelitbangan, 2020)
Abstract: The development of an area must consider the sustainability of the region based on the economic, social and environmental factors. Kota Baru Lampung as a future development center for the central government of Lampung Province really needs to be developed as an environmentally friendly region. Green lane road is part of the landscape in the right of way area (r.o.w) which has the function of safety and comfort to road users, supporting educational activities, recreation and conservation, aesthetics and identity of the area as well as forming the character of a city. The function of plants on the road landscape is to reduce exposure to direct sunlight and vehicle lights, as a guide, physical barriers, controlling movement, controlling microclimate, and animal habitat. This study aims to evaluate the right of way area (r.o.w) as a green road from aesthetic, comfort and safety functions, designing right of way (r.o.w) in accordance with regulations with attention to the principles of sustainable road development. Based on evaluation results, there are several things which stems from interpretations of the information (data) resulted from the evaluation, which are: 1.) The development of a new area must adhere to the principles of sustainable road development so that the negative impacts from the development of an area can be minimized. 2.) The condition of right of way (r.o.w) and the planning of the Kota Baru master plan need to be evaluated to meet environmental standards that are required to have a minimum of 20% open green space (RTH), by applying the principles of environmentally sound road development. 3.) The design concept of right of way that has an environmental insight, should be implemented and promoted in every development of an area.